inCu-click: DNA-enhanced ligand enables live-cell, intracellular click chemistry reaction with copper catalyst - Keqing Nian; Yifang Liu; Yuchen Qiu; Zhuoyu Zhang; Laura Brigandi; Meni Wanunu; Sara H. Rouhanifard (Nature Communications)
Abstract Labeling cellular biomolecules via copper-catalyzed azide–alkyne cycloaddition (CuAAC) offers rapid reaction kinetics and uses small azide and alkyne probes that minimally disturb molecular function, making it ideal for tracking biomolecules. However, applying CuAAC inside living cells has been hindered by the high copper levels required, which compromise cell health. To overcome this barrier, here, we develop inCu-click, an intracellular CuAAC approach that employs a DNA-conjugated ligand (BTT-DNA) to localize and concentrate copper ions at the reaction site. This design permits efficient click chemistry at low intracellular copper concentrations without added copper salts and supports template-driven proximity and liposomal delivery of the ligand into cells. Here we show that inCu-click enables robust fluorescent labeling of nascent phospholipids and proteins in live cells with negligible impact on viability, establishing a platform for real-time visualization of biomolecule dynamics in complex, live cell environments.